Point scintillator dosimetry in ultra-high dose rate electron "FLASH" radiation therapy: A first characterization. (November 2022) - Vanreusel, Verdi; Gasparini, Alessia; Galante, Federica; Mariani, Giulia; Pacitti, Matteo; Cociorb, Madalina; Giammanco, Andrea; Reniers, Brigitte; Reulens, Nathalie; Shonde, Tunde Blessed; Vallet, Hugo; Vandenbroucke, Dirk; et al.
Abstract: FLASH radiation therapy is a novel technique combining ultra-high dose rates (UHDR) with very short treatment times to strongly decrease normal tissue toxicity while preserving the anti-tumoral effect. However, the radiobiological mechanisms and exact conditions for obtaining the FLASH-effect are still under investigation. There are strong indications that parameters defining the beam structure, such as dose per pulse, instantaneous dose rate and pulse repetition frequency (PRF) are of importance. UHDR irradiations therefore come with dosimetric challenges, including both dose assessment and temporal ones. In this work, a first characterization of 6 real-time point scintillating dosimeters with 5 phosphors (Al 2 O 3 :C, Mg; Y 2 O 3 :Eu; Al 2 O 3 :C; (C38 H34 P 2 )MnBr 4 and (C38 H34 P 2 )MnCl 4, was performed in an UHDR pulsed electron beam. The dose rate independence of the calibration was tested by calibrating the detector at conventional and UHDR. Dose rate dependence was observed, however, further investigation, including intermediate dose rates, is needed. Linearity of the response with dose was tested by varying the number of pulses and a linearity with R 2 > 0.9989 was observed up to at least 200 Gy. Dose per pulse linearity was investigated by variation of the pulse length and SSD. All point scintillators showed saturation effects up to some extent and the instantaneous dose rate dependence was confirmed. A PRF dependence was observed for the Al 2 O 3 :C, Mg and Al 2 O 3 :C- based point scintillators. This was expected as the luminescence decay time of these materials exceeds the inter-pulse time. Highlights: Point scintillator dosimetry as promising real time solution for FLASH radiotherapy. Point scintillator detectors allow linear calibration with dose. Luminescence decay time is the limiting factor for point scintillators in FLASH. Saturation with dose per pulse is caused by luminescence decay time.